1840-1856 YILLARI ARASINDA RUSYA`NIN BALKAN POLİTİKASI VE BU POLİTİKA ÇERÇEVESİNDE OSMANLI İMPARATORLUĞU İLE İLİŞKİLER - USLU, ADEM (Fırat Üniveristesi, 2007)
[Abstract Not Available]
Russia's policy towards the Balkans between the years 1840-1856 and her relations with the Ottoman Empire in this context
Keywords: Tarih